"They know what they are getting into:" Researchers confront the benefits and challenges of online recruitment for HIV research. Issue 7 (2nd October 2020) - Bragard, Elise; Fisher, Celia B.; Curtis, Brenda L.
ABSTRACT: Online research has become a critical recruitment modality for understanding and reducing health disparities among hidden populations most at risk for HIV infection. There is a lack of consensus and guidelines for the responsible conduct of online recruitment for HIV risk populations. Using semi-structured phone interviews, this study drew on the experiences of principal investigators (PIs) engaged in online HIV research to illuminate scientific and ethical benefits and challenges of social media recruitment. Using Thematic Analysis five major themes emerged: sampling advantages and disadvantages; challenges of data integrity; control of privacy protections; researcher competence and responsibility; and resources.